A prática avaliativa da professora da 1ª série em uma escola municipal de Fortaleza: entre o escrito e o vivido - Furlanetto, Cláudia Regina (2007)
The present research aims to understand how learning assessment has been conducted in a municipal school from Fortaleza. Research was done based on official texts (Assessment of the teaching-learning process systematic, municipal syllabus proposal – from kindergarten to 4th grade, Pedagogical directresses for the implementation of educational institutions – municipal day care centers and pre-schools of Fortaleza, Pedagogical-Political and Scholastic Regime project) assessment practice of a 1st grade teacher. The research privileges the qualitative approach, constituting a study which considers phenomenological and ethnographic principles. Besides that, it uses participant observation, interview, and documental research as tools for data sampling. Data analysis reveals that the spaces, materials, professoriate formation, pedagogical monitoring of the teacher, planning, and interaction between family and school are all significant aspects for professoriate assessment practice. Nevertheless, at municipal schools, spaces and materials are not being used in a way that stimulates diversity, which is extremely important for assessment. Moreover, professoriate formation, pedagogical monitoring of the teacher, planning, and interaction between family and school need special care. The aspects listed above influence assessment practice of the 1st grade teacher, who outlines a syllabus distant from the differentiated activities, centered on Linguistics and Logical-Mathematical Knowledge, occasioning an assessment anchored on written activities, far from observations, daily written reports, and interventions possible to put into effect better learning. What is more, despite the teacher’s graduation in Pedagogy and post-graduation in Psychopedagogy and Psychodrama, she is not aware of the assessment theories. The results also show that municipal official texts do not satisfactorily clarify the assessment process and are poorly known within the ambit of the school, and, as a result, the teacher is not oriented by them. This way, professoriate assessment practice develops amongst the previously mentioned difficulties.